2009
DOI: 10.1016/j.jaci.2008.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course and urinary eicosanoids in patients with aspirin-induced urticaria followed up for 4 years

Abstract: Aspirin hypersensitivity manifesting as urticaria/angioedema remains present after 4 years in about two thirds of patients. Aspirin-precipitated skin reactions associate with increased excretion of LTE(4) and PGD(2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 20 publications
3
54
0
Order By: Relevance
“…According to this hypothesis, inhibition of cyclooxygenase by NSAIDs may lead to a decrease in protective prostaglandins production, leading to activation of mediator release from inflammatory cells in the skin. This hypothesis was further supported by observations that skin eruptions after oral aspirin challenge were accompanied by the release of eicosanoids similarly to patients with AERD (49,50).…”
Section: Pathomechanismsmentioning
confidence: 66%
See 1 more Smart Citation
“…According to this hypothesis, inhibition of cyclooxygenase by NSAIDs may lead to a decrease in protective prostaglandins production, leading to activation of mediator release from inflammatory cells in the skin. This hypothesis was further supported by observations that skin eruptions after oral aspirin challenge were accompanied by the release of eicosanoids similarly to patients with AERD (49,50).…”
Section: Pathomechanismsmentioning
confidence: 66%
“…Skin eruptions usually subside within few hours but may persist for several days. The degree of sensitivity to NSAIDs may show temporary fluctuations related to activity of underlying chronic disease and may even disappear in some patients (50). A certain proportion of patients with cutaneous adverse reactions may also develop respiratory symptoms.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Setkowicz et al [53] studied patients with chronic idiopathic urticaria and aspirin hypersensitivity. They followed patients for 4 years, performing aspirin provocations and measuring urinary levels of leukotriene E4 (LTE4) and the main prostaglandin (PGD2) metabolite (9a11bPGF2) at the beginning and at the end of the period.…”
Section: Urinary Eicosanoidsmentioning
confidence: 99%
“…NERD and NECD are considered to be caused by a nonspecific immunological mechanism whereby NSAIDs inhibit COX enzymes, leading to a dysregulation of leukotriene homeostasis [7]. Since Szczeklik associated the capacity of NSAIDs to block the COX-1 enzyme with asthma exacerbations [10], many studies on the basis of this hypothesis have been published [11][12][13][14][15][16][17][18][19][20]. However, despite considerable study, there is a lack of evidence to support this hypothesis for NIUA [7].…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been shown that these patients have higher basal LTs levels that are augmented after drug intake [13][14][15]20] and related to the severity of symptoms [25]. This dysregulation is not only found for NERD patients; in fact, NECD patients also show high levels of LTs [17,19]. However, little evidence exists for NIUA [20].…”
Section: Introductionmentioning
confidence: 99%